ANALISIS KEPUASAN NASABAH PADA PT. BANK PERKREDITAN RAKYAT EKA BUMI ARTHA CABANG KALIANDA LAMPUNG SELATAN - Herwanto - (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2014)
PT. Bank Perkreditan Rakyat Eka Bumi Artha of Kalinda South Lampung is a company(Bank) which established in service field to the society, As a bank which tries to give the bestservices with the expectation that be able to give the satisfactory and contribution to customers’prosperous. It is related to the slogan “Giving the best service”. From analysis result and discussingcan be concluded that service quality which consists of shape, attention, quick respond, master andcertainty simultaneously and partially influences positively and significantly toward customers’satisfactory. In simultaneously, it can be proven by the accumulation result that F count is 17,6553 isbigger than F table score with dk numerator = 5 and dk denominator = 94 at trust level 95% = 2,311.Inpartially all t count score which consists of bigger than t table score. It is proven that service qualitywhich consists of shape, attention, quick respond, master and certainty influence positively andsignificantly toward customers’ satisfactory.